Disaster Management for the Production Process in Manufacturing Industries - Bhojraj N Kale; Prakash V Dhopte; Pravin T Petkar; Bhushan B Deshmukh; Safal A Shambharkar; Sanjay A Sajjanwar (International Journal of Manufacturing and Production Engineering, 2026)
In manufacturing and businesses in general, damages occurring during production must be recorded. Production is carried out continuously every day through various processes that make up the supply chain. This process is often ineffective and causes damage. These disasters cause economic damage and losses, sometimes even death. These damages may result from accident, negligence or incompetence. There are other things around. This article focuses on damage elements associated with the manufacturing process. These attributes include: disaster management (prevention and mitigation), disaster duration (before, during and after the disaster), disaster type (interaction accident, fire). This article describes collaboration between higher education and industry in disaster reduction to educate workers and businesses involved in production on the importance of environmental management. This is an area of research that no company should ignore in the production process. In addition to these aspects, the role of modern technology such as automation, real-time monitoring systems, and data analytics has become increasingly important in identifying and reducing potential risks in production environments. Implementing strict safety protocols, regular maintenance of machinery, and continuous training programs for employees can significantly minimize the occurrence of such damages. Furthermore, establishing effective communication channels within the organization ensures that any potential hazards are reported and addressed promptly. Sustainable practices and adherence to environmental regulations also contribute to reducing long-term risks and improving overall production efficiency. Therefore, integrating technological advancements with proper management strategies can enhance safety, reduce losses, and promote a more resilient manufacturing system.
Keywords: Workplace safety; disaster; economic loss; management; production process; supply chain inefficiency